44 Pre-hospital kit and error reporting system (kers): safety for students. (17th November 2016) - Taylor, S; Eccles, S; Wong, A; Gopal, A
Abstract : Background: The Hull York Medical School Pre-Hospital Care Programme (HYMS PCP) aims to develop medical student interest in pre-hospital care. 1 Clinical education is achieved through training, qualification and experience as community first responders with Yorkshire Ambulance Service 2 and Lincolnshire Integrated Voluntary Emergency Services (LIVES), 3 providing pre-hospital care in the community. With 60 members at different stages of training, medical equipment and medication across 5 schemes, fixing unserviceable kit and prompt resupply requires meticulous tracking which is vital to patient and student safety. A need has been identified to monitor equipment and if necessary, a mechanism to raise potential concerns anonymously. Methodology: A kit audit was performed and a handover form created to flag issues pertaining to kit condition. Each responder completes the online form as part of handover. This flags issues to the responder co-ordinator who can rectify or escalate issues promptly. A secondary form allows anonymous reporting of safety concerns. These are reviewed by the governance and development team responsible for the PCP, where issues were addressed or escalated where necessary. Anticipated outcomes: The current mechanism of escalation directly to the respective professional organisation (YAS or LIVES) remain intact and encouraged. Our internal reporting system facilitates open discussion of non-urgent concerns. These are currently being piloted in our LIVES units. A re-audit, responder survey incorporating validated aspects of the Safety Attitudes Questionnaire, 4 and review of all changes instigated at three and six months will assess the benefit of KERS to our students and patients. We intend to present our qualitative and quantitative results at the conference. Impact: These changes are intended to encourage an organisational safety culture amongst undergraduate healthcare professionals to take forward into their professional careers. We intend to disseminate our results to encourage similar student organisations to adopt similar approaches to improve safety. References: Wong A, Pham K, Preece J. A new approach to undergraduate pre-hospital education. Poster session presented at: BASICS conference; 2013 Oct 11–12; Dudley, West Midlands, UK. Community First Responders Yorkshire Ambulance Service. Yorkshire Ambulance Service NHS Trust, United Kingdom; [cited 2016]. Available from: http://www.communityresponders.yas.nhs.uk/. LIVES. LIVES Responders. LIVES.org.uk. [cited 2016]. Available from: http://www.lives.org.uk/about-us/responders/. Sexton JB, Heimreich RL, Neilands TB, Rowan K, Vella K, Boyden J, Roberts PR & Thomas EJ. The safety attitudes questionnaire: psychometric properties, benchmarking data, and emerging research. BMC Health Serv Res 2006;6 :44.